Seeking Truth from Doubts and Seeking Truth from Mistakes: A Study on Strategies to Improve the Effectiveness of Biological Experiment Teaching - Wu, Xiaozhang; Yang, Di; Guo, Yuanyuan (Journal of Education and Educational Technologies, 2023)
Dalian University of Science and Technology attaches great importance to the construction of teacher ethics and professional conduct. Firstly, it has always adhered to the construction of teacher ethics and professional conduct as the first lesson for teachers to enter the school. This course is personally taught by the secretary of the school party committee, and each new teacher will participate in a collective teacher ethics oath activity after this event. Secondly, all school teachers are required to establish a file of professional ethics and conduct, and solemnly sign a commitment letter of professional ethics and conduct. Once again, the School Teacher Teaching Development Center invites exemplary teachers' ethics to conduct thematic reports on campus every year. In 2019, the school invited Professor Qu Jianwu, a model of the times, to participate in a themed lecture on the construction of professional ethics and conduct for all teachers, especially young teachers. All teachers were deeply moved and encouraged. Finally, the Propaganda Department of the School Party Committee promotes and publicly reports on the role models of the school's teacher ethics through internal media, striving to create ideological orientation of 'teacher ethics first'.